Effect of distance to urban center on the value of rural land: the case of Guapiles - Paniagua Molina, Javier (2018)
A research was carried out to determine the effect of the distance to the city of Guapiles on the value of the rural lands in the surroundings of this city. It was determined that the unit value per square meter declines exponentially as the distance, measured in kilometers, increases with a regression coefficient of -0.023.  The model showed that land size and distance to urban center accounted for 89% of the variability in the unit value of rural land.  The explosion of the accelerated development of the city of Guápiles has generated a pressure on the value of the land, as well as expectations, sometimes too high for the owners of the land.